UNIT 9.5 Molecular Analysis of Fragile X Syndrome. (21st January 2014) - Basehore, Monica J.; Friez, Michael J.
Abstract: The gene responsible for Fragile X syndrome, fragile X mental retardation‐1 ( FMR1 ), contains an unstable sequence of CGG trinucleotide repeats in its promoter region. Expansions of >200 trinucleotide repeats are considered full mutations and typically lead to abnormal methylation of the region, resulting in loss of FMR1 expression. Males with loss of FMR1 protein are expected to be affected by Fragile X syndrome, while females may or may not clinically manifest features of the condition. The protocols in this unit outline the complementary use of polymerase chain reaction (PCR) and methylation‐sensitive Southern blot hybridization to accurately measure trinucleotide repeat size and methylation status. These protocols are also used to evaluate CGG repeat size in two adult‐onset conditions known for their association with FMR1 premutation alleles, Fragile X Tremor/Ataxia (FXTAS) syndrome and Premature Ovarian Failure (POF). Curr. Protoc. Hum. Genet . 80:9.5.1‐9.5.19. © 2014 by John Wiley & Sons, Inc.